the PENGARUH BRAND AMBASSADOR DAN BRAND IMAGE TERHADAP PROSES KEPUTUSAN PEMBELIAN PADA KATERING DIET ‘YELLOWFIT KITCHEN’: THE INFLUENCE OF BRAND AMBASSADOR AND BRAND IMAGE ON THE PURCHASE DECISION PROCESS IN 'YELLOWFIT KITCHEN' DIET CATERING - Gemintang Chalista Romli; Kristina Sisilia (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The purpose of this study is to determine how much influence Brand Ambassadors and Brand Image have on purchasing decisions on the YellowFit Kitchen Catering diet. YellowFit Kitchen is still relatively new compared to incumbents in the catering industry but has higher popularity than its competitors and has a sales turnover in the last three years reached IDR 250 billion in 2022. The method used is a quantitative method with a descriptive research type. The population used in this study is consumers who have purchased YellowFit products and know Clarissa Putri as a Yellowfit Brand Ambassador, with a sample size of 100 respondents with the purposive sampling method. The result shows that the Brand Ambassador and Brand Image variables are included in the good category with a significant simultaneous and partial influence on the Purchase Decision of YellowFit Kitchen Catering diet products. The Brand Ambassador variable (X1) has a significant effect on the Purchase Decision (Y), and the Brand Image variable (X2) also has a significant effect on the purchase decision at the Catering Diet YellowFit Kitchen. The coefficient value of the determinant of the influence of Brand Ambassador and Brand Image, on Purchase Decision, is 54.5%. The remaining 45.5% is influenced by other factors not examined in this study